Technology, crime, and justice: the question concerning technomia - McGuire, M. R. (Routledge, 2012)
Introduction -- Technology and it technomia -- Foundations : from echotechnic harm to industrial justice -- Tele-crime : misusing information communication technologies -- Tele-control : from police whistles to the post-surveillance society -- Micro-crime : misusing chemical, biological and nuclear technologies -- Micro-control : CBNTs and the biochemical citizen -- Of hairdryers, hammers, and handguns : mid and multi-range technologies -- Science, technology, and justice -- The question concerning technomia